Domestic queens under natural temperate photoperiod do not manifest seasonal anestrus - Faya, Marcela Inés (2011)
Domestic cat seasonality between the tropics and the arctic zones is scarcely described and results are inconsistent. The aim of this study was to describe domestic feline seasonal patterns under a natural temperate photoperiod. A total of 372 estrous cycles were studied in 34 post pubertal cats during 900 days. The queens were housed in a cat colony (31°25' South Latitude, 64°11' West Longitude), acclimated under natural photoperiod and daily observed for reproductive behavior. Vaginal cytology was conducted three times a week. For each cat the number of estrous cycles and days in estrus per month for each year were recorded. The months of the year were grouped in four periods of 3 months each according to day length and photoperiod. Comparisons of estrous days among periods were performed by ANOVA for repeated measures. All the cats had estrous cycles throughout the year without intervals of anestrus. Mean number of estrous days differed among the periods (P<0.01), those of long day length and ascending photoperiod being greater (12.5±0.6) to those of descending photoperiod either with long (8.9±0.7) or short (9.3±0.7) days. When the two periods with ascending day lengths were merged and compared to the two periods with descending day lengths merged, the number of estrous days were greater when day length ascended (P<0.01). Nearly 60% of the estrous cycles occurred during the periods of ascending day length. It is concluded, that domestic cats under natural temperate photoperiod have estrous cycles throughout the year showing peak activity the months with increasing photoperiod.